Efficiently optimized multi-fillers for rain gardens: Long-term pollution control performance - Tianyin Huang; Zhixin Wang; Yiming Nie; Hanhan Liu; Peirong Li; Jingjing Yang; Bingdang Wu (Water Cycle)
Rain gardens play a pivotal role in the infiltration and purification of runoff, with the filler layer being a critical component. However, the selection and configuration of fillers in existing rain gardens often lack scientific rigor, leading to suboptimal performance. To address this issue, this study employs the Analytic Hierarchy Process (AHP) to systematically evaluate 11 types of fillers, including 5 natural materials, 3 industrial wastes, and 3 artificial materials, aiming to optimize filler configurations and enhance the pollutant removal efficiency of rain gardens. The results demonstrate that steel slag, coconut shell biochar, green zeolite, and fly ash ceramic granules exhibit superior performance in purifying both simulated and actual runoff. The optimal filler combination, comprising 25% green zeolite, 25% steel slag, and 50% coconut shell biochar, achieved removal rates of 50.49%, 76.12%, 44.12%, 89.94%, 58.38%, and 88.19% for COD, NH4+-N, TP, Cu(II), Cr(VI), and tetracycline, respectively. Long-term operational evaluation (>110 days) revealed that the optimized filler layer significantly improved the removal rates of COD, TN, and TP to 86.83%, 80.19%, and 88.42%, respectively. By comparing the physicochemical properties of the fillers before and after use, the mechanisms underlying runoff purification were preliminarily elucidated. Different fillers exhibited specific adsorption capabilities for distinct pollutants, and the synergistic effects of multiple fillers significantly enhanced the rain garden's capacity for source pollutant reduction. AHP was used in this study to validate the scientific validity of AHP in the device of rain gardens through filler combination adsorption experiments and long-term monitoring of rain garden installations, while concurrently offering a broader range of green solutions for the enhancement of rain gardens.